LANGUAGE AND COGNITION: EXAMINING THE ROLE OF APOHA IN BUDDHIST THEORIES OF MEANING AND SEMANTICS - Naik, Babuli (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The Buddhist theory of Apoha (exclusion) offers a distinct and non-essentialist approach to meaning and cognition by rejecting intrinsic universals and elucidating linguistic categorization through negation. Rooted in the epistemological and logical traditions of Indian Buddhism, Apoha was systematically formulated by Dignāga and Dharmakīrti as a counterargument to realist theories of meaning, which assert the existence of inherent essences corresponding to linguistic categories. Instead of postulating a positive universal, Apoha posits that words acquire meaning by excluding what they do not denote. For instance, the term "cow" does not signify an inherent cow-ness but instead differentiates cows from non-cows. This exclusion-based model of meaning challenges ontological realism and presents an alternative perspective in which meaning is derived through negation rather than intrinsic identity. This paper examines Apoha in relation to contemporary cognitive science, particularly in the contexts of category formation, prototype theory, and conceptual blending. Empirical research in cognitive science indicates that human categorization operates through flexible, context-sensitive processes rather than rigid universals, thereby aligning with the Buddhist view that meaning is constructed rather than inherent. Engaging with contemporary debates in the philosophy of language and cognitive semantics, this study positions Apoha in dialogue with alternative theoretical frameworks, including Aristotelian essentialism, Fregean reference theory, and Wittgensteinian perspectives on language. Through this comparative analysis, the paper explores how Apoha challenges foundational assumptions concerning meaning, reference, and conceptual representation. Furthermore, this study critically engages with objections to Apoha, particularly those advanced by the Nyāya School, which argues that exclusion alone is insufficient for a comprehensive account of linguistic meaning. Nyāya philosophers contend that Apoha leads to an infinite regress or circular reasoning, as negation presupposes some form of positive content. By reassessing these critiques within the framework of cognitive science, this paper demonstrates how Apoha can be reinterpreted as a viable model for understanding the construction and communication of meaning, particularly in light of contemporary non-essentialist approaches to language. By integrating Buddhist epistemology with modern linguistic and cognitive theories, this study highlights the enduring significance of Apoha in contemporary discussions on language and cognition. The exclusion-based model of meaning proposed by Apoha aligns with non-essentialist and usage-based linguistic frameworks, offering valuable insights into how meaning is generated through contrast, differentiation, and contextual dependence. In doing so, this research underscores Apoha not only as a pivotal contribution to Indian philosophy but also as a theoretically robust and philosophically compelling framework for modern cognitive and linguistic inquiry.